Traceability of animal byproducts in quail (Coturnix coturnix japonica) tissues using carbon (13C/12C) and nitrogen (15N/14N) stable isotopes - Móri, C. [UNESP]; Garcia, Edivaldo Antonio [UNESP]; Ducatti, Carlos [UNESP]; Denadai, J. C. [UNESP]; Pelícia, K. [UNESP]; Gottmann, R. [UNESP]; Mituo, A. O. M. [UNESP]; Bordinhon, A. M. [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2007)
Consistent information on meat products consumed by the public is essential. The technique of stable isotopes is a powerful tool to recover consumers' confidence, as it allows the detection of animal byproduct residues in poultry meat, particularly in quail meat. This study aimed at checking the presence of poultry byproduct mixtures in quail diets by applying the technique of carbon (13C/12C) and nitrogen (15N/14N) stable isotopes in quail breast muscle, keel, and tibia. Sixty four one-day-old male quails were obtained from a commercial farm. Birds were housed in an experimental house from one to 42 days of age, and were randomly distributed into 8 experimental treatments, and fed diets containing poultry offal meal (POM), bovine meat and bone meal (MBM) or poultry feather meal (PFM), or their mixtures. Four birds per treatment were slaughtered at 42 days of age, and breast (Pectoralis major), keel, and tibia were collected for analyses. The inclusion of animal byproducts in quail diets was detected by 13C e 15N analyses in the tissues of the birds; however, it was not possible to specify which byproducts were used. It was concluded that quail meat can be certified by the technique of stable isotopes.
Keywords: Animal byproducts; certification; meat quails; stable isotopes